PENDEKATAN AL-QUR’AN DALAM MENGATASI TRAUMA ANAK BROKEN HOME DALAM Q.S. Al-BAQARAH AYAT 286 ( KAJIAN TAFSIR AL-MARAGHI) - Almi, Muhammad; Hermanto, Edi; Hidayatullah, Mhd.Raihan; Putri Astuti, Wida; Masitoh Harahap, Siti (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
The Al-Qur'an is the holy book of Muslims which was revealed to the Prophet Muhammad SAW through the Angel Jibril Alaihissalam gradually over 23 years. The Al-Qur'an has many names, one of which is asy Syifa which means healing medicine, this is in line with the word of Allah which meaning, O people, a lesson (Al-Qur'an) has come to you from your Lord, a cure for diseases in the chest and guidance and mercy for believers, so the author tries to provide a solution to broken home children through the Al-Qur'an approach An, the research method used by the author in this research is a qualitative method with a descriptive approach, while the data collection technique in this research is literature study by searching for rivew literature through journals, magazines, theses, books and other rivew literature. The results of this research are to provide a solution to children whose parents have abandoned them due to psychological factors in the form of jealousy towards each other and declining or low economic conditions in the household, so that in this case the child becomes a victim both physically and mentally.